Effect of gamma irradiation on harvest date of local upland red rice cultivar. Issue 1 (February 2020) - Muhidin,; Syam'un, E; Kaimuddin,; Musa, Y; Sadimantara, G R; Leomo, S; Sutariati, G A K; Yusuf, D N; Rakian, T C
Abstract: Rice is a carbohydrate sources and main staple food in Asia including Indonesia. The aim of the study is to assess the effect of gamma irradiation on the harvest date of upland rice. Common problems in cultivation of upland red rice are low production and long harvest life. One of the solutions is through the breeding mutation. The research was conducted in Field Experiment Faculty of Agriculture, Halu Oleo University. The research used a split plot design, as main plot was the irradiative treatment and the sub plot was the different of cultivar in three replications. The irradadiative treatment consist of two levels, i.e. b0 =without gamma irradiation, b1 = treatment with gamma irradiative. The cultivar tested are (v1 ) = Labandiri, (v2 ) = Jangkobembe, (v3 ) = Ranggohitam, (v4 ) = Paedara . The research reveals that gamma irradiation treatment could accelerate the plants to reach the age of flowering, simultaneity of flowering, seed filling period, and harvest date.